Genetic and clinical studies in autosomal dominant polycystic kidney disease type 1 (ADPKD1). - Coto, E (1992)
Thirteen Spanish families with autosomal dominant polycystic kidney disease were studied. In one family the disease did not segregate with polymorphic markers around the PKD1 locus. All subjects over the age of 30 years carrying a mutation at the PKD1 locus showed renal ultrasonographic cysts, but 40% of carriers of the PKD1 mutation younger than 30 years did not have renal cysts. Hypertension was found to be more frequent in those with renal cysts. Recombinants between 16p polymorphic loci and the PKD1 locus are described.